Fear of Success Is Everywhere: Fake or Real? - Agus Robi Widiyansa; Dwinto Martri Aji Buana (Technium Social Sciences Journal, 2021)
Every human has what it takes to get past whatever they are going through if they decide to push through it. Tragedy and trials come to everybody. Only the strong can survive because the journey to our dreams always starts from within. Engle (2003) says that fear of success is a condition when a person gets fear of disruption of its ability to complete a task or job that is challenging. The next dimension is not only looking at fear of success, but elaborate on the negative effect, field of research, and decision-maker participation against the fear of success. The purpose of this study was to assess fear of success whether it occurs in various places, fields, and also in each individual. This research method is a review of various previous literature studies. The results showed that fear of success occurred in various places, fields, and identified in various individuals. Several suggestions and managerial implications are also put forward at the end of this paper. Originality for this paper analyzes the literature on fear of success from the point of view of various contexts, and the paper type in the preparation of this study is in the form of a literature review.